Causes of crime in Kenyan universities - Kombo, Paul (My University, 2016)
This study investigated the causes of crime in Kenyan public universities which had been reported to be an upward trend. Criminological theoretical models suggest factors such as neighbourhoods, parenting poverty and peer pressure (among other factors), have a relationship with crime causation. Overcrowding in the public universities has been an issue of concern to university managements and government in recent years. Utilising the routine activity, social media disorganisation, environmental influence, crime resistance and susceptibility theoretical models, the study sought to examine both neighbourhoods and overcrowding as its objectives. The study also looked at radicalisation into extremism given that it impacts our universities after cases of students being recruited and inducted into extremism had been conducted by police and the media. Two approaches were used in this study to examine radicalisation studies. On the one hand, are models defining radicalisation as a process using theological and vulnerability models claimed to be used to justify counterterrorism measures. The second model comprises critiques who have questioned counterterrorism approaches based on these factors. Mainly using the qualitative method of data collection, the study used a questionnaire with carefully formulated questions to elicit rich information for analysis. A large percentage of respondents (91%) agreed that they learned behaviors not to engage in criminality in their neighbourhoods. An even higher percentage (95%) agreed that good morals taught by parents helped them to keep away from deviant behaviour. Another 82% agreed that overcrowding was a cause of crime in in universities while 76% agreed that the promises of financial and other benefits induced students to join terrorism. Findings also show agreement that serious forms of crime notably robbery 82%, stealing 82%, forgery and assaults 72%, are prevalent. The conclusions are that neighbourhoods play critical roles in the shaping of children’s thoughts on whether to engage or not to engage in deviant behaviour. Secondly, it was shown that overcrowding causes crime and lastly there was confirmation that students joined terrorism due to promises of financial and other benefits. These conclusions imply the need to find ways of improving neighbourhood environments by providing amenities and facilities to deal with poverty and deprivation. Overcrowding can be similarly addressed through provision of adequate funding for construction of necessary infrastructure. These need to be dealt with by formulating poverty reduction strategies targeting the poorest communities and areas. The prevalence of serious crimes implies need for the improvement of campus security systems.
Keywords: Crime; Criminology; Radicalization